An Exploratory Comparison Of Dominant And Non-Dominant Foot Passing Ability In Junior High School Futsal Students - Femmi Kristianse Lutemadi; Ahmad Faiz Islami; Muhammad Arham; Muh. Maula Tirta; Ofelwanto Ofelwanto (CV Lentera Cendekia Indonesia, 2026)
Introduction. An imbalance in ability between the dominant and non-dominant foot is a common fundamental technique problem among school-age futsal players. Various studies have shown that young players are more skilled when using their dominant foot, while their non-dominant foot is less trained, resulting in lower coordination and accuracy. This imbalance impacts passing quality, movement stability, and decision-making on the pitch. Objective. This study aims to analyze and compare the passing ability of students using their dominant and non-dominant feet participating in futsal extracurricular activities at SMP Negeri 8 Makassar. Methods. This study used a quantitative approach with a comparative design. The sample consisted of five students selected through purposive sampling. The research instrument was a passing accuracy test consisting of ten trials for each leg from a distance of 10 meters. Data analysis was condusted descriptively and using a paired t-test. Results. The results showed that the average passing score of the dominant foot was 5.0 (SD = 1.00), while the non-dominant foot was 3.6 (SD = 1.14). the t-test results showed a p value of 0.206 (p>0.05), which means there was no significant difference between the passing ability of the dominant and non-dominant feet. However, the mean score showed that the dominant foot still had a higher level of accuracy. Conclusion. There was no significant difference between dominant and non-dominant foot passing ability in students at SMP Negeri 8 Makassar. However, there was greater variation in performance with the non-dominant foot, so bilateral training is essential to improve stability, coordination, balance, and basic futsal technical skills.